A Review of the Literature on the Functional Analysis of Inappropriate Mealtime Behavior. Issue 1 (January 2020) - Hodges, Abby; Davis, Tonya N.; Kirkpatrick, Marie
A functional analysis is a well-established and widely used assessment in the treatment of challenging behavior. Given the fact that functional analysis results can inform treatment selection and procedures, a review of the current literature regarding functional analysis of inappropriate mealtime behavior (IMB) is warranted as it may guide researchers in conducting a functional analysis prior to treating IMB. This review summarizes the literature regarding functional analysis of IMB. Fourteen studies that implemented a functional analysis of IMB were identified and summarized based on procedural components of the functional analysis, results, and treatment selection. Results indicate functional analysis of IMB to be effective in the identification of variables maintaining IMB. Although functional analysis of IMB has been found to be helpful, several areas for further research and evaluation are identified.